Justice based corruption eradication policy: A comparison between Indonesia and Denmark - Siagian, Fahrizal S.; Lubis, Andi Hakim; Salwa, Nabila Afifah; Firouzfar, Saied (Integritas: Jurnal Antikorupsi, 2024)
: This research was conducted to obtain an explanation of corruption eradication policies in Denmark and Indonesia. In addition, to find out the justice-based corruption eradication policy in a comparative study of Indonesia and Denmark. This research uses a normative juridical method with a literature study. Based on this, the required results are that corruption eradication policies in Indonesia and Denmark have significant differences. Denmark inserts corruption eradication provisions into each of its laws and regulations and uses a strict element of transparency in state financial management. Denmark utilizes social sanctions supported by the legal culture of its highly law-abiding society. Second, the policy reconstruction that can be used in Indonesia to eradicate corruption adopts the Danish policy. Namely, the anti-corruption agency with independent status integrates corruption eradication regulations into national legislation emphasizing strict sanctions and transparency of state financial management correlated with the wealth of state officials. The independence of the Corruption Eradication Commission is crucial. Applying Denmark’s mechanisms could lead to a breakthrough in corruption eradication in Indonesia.